2015
DOI: 10.1111/myc.12352
|View full text |Cite
|
Sign up to set email alerts
|

The role of fungal sensitisation in clinical presentation in patients with chronic obstructive pulmonary disease

Abstract: Atopic patients with chronic obstructive pulmonary disease (COPD) demonstrate more severe symptoms than their non-atopic counterparts. Also, Aspergillus hypersensitivity is known in COPD. However, allergic sensitisation to non-Aspergillus fungi has never been studied in COPD patients. To evaluate the prevalence of fungal sensitisation and its impact on the clinical presentation and outcome of COPD patients. Sensitisation to 17 fungi was studied in 55 COPD patients through skin prick tests, fungus-specific IgE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…11,13 Recently, Agarwal et al reported sensitisation to non-Aspergillus fungi in three of the 55 (5.5%) COPD subjects studied. 20 The results of these studies suggest that fungal sensitisation does occur in COPD and the differences in prevalence could be related to the method used for the diagnosis of fungal sensitisation (skin testing or fungal-specific IgE or both). We have previously demonstrated that A. fumigatus-specific IgE is more sensitive than Aspergillus skin test for the diagnosis of ABPA.…”
Section: Discussionmentioning
confidence: 95%
“…11,13 Recently, Agarwal et al reported sensitisation to non-Aspergillus fungi in three of the 55 (5.5%) COPD subjects studied. 20 The results of these studies suggest that fungal sensitisation does occur in COPD and the differences in prevalence could be related to the method used for the diagnosis of fungal sensitisation (skin testing or fungal-specific IgE or both). We have previously demonstrated that A. fumigatus-specific IgE is more sensitive than Aspergillus skin test for the diagnosis of ABPA.…”
Section: Discussionmentioning
confidence: 95%
“…Also, sensitization against S . commune has been reported in patients with COPD, but the clinical implication of this needs to be established [ 11 ]. Further, FACC is mainly reported from Japan [ 5 ].…”
Section: Spectrum Of Noninvasive Diseases Caused By Fbmmentioning
confidence: 99%
“…The FBM B . adusta has been shown to colonize the pharynx of susceptible individuals and produce a chronic uneasiness that produces the cough [ 11 ]. In FACC patients, FBM have been found in induced sputum cultures [ 5 ].…”
Section: Spectrum Of Noninvasive Diseases Caused By Fbmmentioning
confidence: 99%
See 1 more Smart Citation
“…For several years, growing investigations have supported the association of particular species of Rhizopus with bronchial asthma and other types of allergy (5)(6)(7)(8)(9)(10). In India, emerging clinical and immunological studies have suggested the involvement of Rhizopus oryzae allergens in type I allergy (11)(12)(13). Rhi o 1 is a major allergen (aspartic protease, molecular mass 44 kDa) of R. oryzae, which causes respiratory sensitization to mold allergic patients (14).…”
Section: Gaekn-wagqyvvdcnk) Of Rhi O 1 That Frequently Reacted With Igementioning
confidence: 99%